A novel peptide mimetic, brilacidin, for combating multidrug-resistant Neisseria gonorrhoeae - Abdallah S. Abdelsattar; Nader S. Abutaleb; Mohamed N. Seleem (PLoS ONE, 2025)
Neisseria gonorrhoeae is classified by the Centers for Disease Control and Prevention as an urgent public health threat due to rising infections and rapid resistance development. N. gonorrhoeae has developed resistance to nearly all FDA-approved drugs, with ceftriaxone being the only remaining effective treatment for gonococcal infections. Alarmingly, ceftriaxone-resistant N. gonorrhoeae strains were isolated worldwide, raising the potential of untreatable gonorrhea in the near future. Hence, the critical need to develop new anti-N. gonorrhoeae therapeutics cannot be overemphasized. In this study, we identified the peptide mimetic brilacidin as an effective anti-gonococcal agent. Brilacidin completed phase 2 clinical trials for treating skin infections, oral mucositis, and COVID-19. Herein, brilacidin displayed potent activity against a panel of 22 drug-resistant strains of N. gonorrhoeae, inhibiting 50% of the strains tested (MIC50) at the concentration of 4 µg/mL. The peptide exhibited rapid bactericidal activity, reducing N. gonorrhoeae high inoculum within two hours. Moreover, brilacidin was superior to the drug of choice, ceftriaxone, in eliminating the intracellular N. gonorrhoeae harbored within endocervical cells. Additionally, brilacidin showed high tolerability in mammalian cells and lacked hemolytic activity in human erythrocytes. Altogether, the results demonstrate that brilacidin is a promising anti-gonococcal agent that warrants further in-depth investigation.